Pengaruh Return On Assets (ROA) dan Return On Equity (ROE) terhadap Harga Saham PT Unilever Indonesia Tbk Periode 2018–2022 - Pretty Naomi Sitompul; Selvia Fransiska Wijaya (CV. ITTC INDONESIA, 2025)
This study aims to examine the impact of Return On Assets (ROA) and Return On Equity (ROE) on the stock price of PT Unilever Indonesia Tbk over the 2018–2022 period. The research utilizes secondary data derived from the company’s published financial statements. The methodology involves multiple linear regression analysis to evaluate the influence of these two independent variables on stock price as the dependent variable. The results indicate that ROA and ROE collectively have a significant effect on stock price. However, when analyzed individually, ROA exhibits a stronger influence compared to ROE. This research is intended to provide valuable insights for investors in understanding the factors that influence stock prices.